2021
DOI: 10.1007/s10461-021-03278-w
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of an Intervention to Promote Viral Suppression and Serostatus Disclosure for Men Living with HIV in South Africa: Qualitative Findings

Abstract: Men living with HIV (MLWH) often have reproductive goals that can increase HIV-transmission risks to their pregnancy partners. We developed a safer conception intervention for MLWH in South Africa employing cognitive behavioral skills to promote serostatus disclosure, ART uptake, and viral suppression. MLWH were recruited from an HIV clinic near Durban, South Africa, and encouraged to include partners in follow-up visits. Exit in-depth interviews were conducted with eleven men and one female partner. The emerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 71 publications
0
14
0
Order By: Relevance
“…Another approach is to focus on male partner engagement as a way to increase SC uptake [ 87 , 88 ]. Male partners have a strong impact on fertility and SC decisions [ 18 , 24 , 25 , 31 , 33 ] and interventions that acknowledge these dynamics are needed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another approach is to focus on male partner engagement as a way to increase SC uptake [ 87 , 88 ]. Male partners have a strong impact on fertility and SC decisions [ 18 , 24 , 25 , 31 , 33 ] and interventions that acknowledge these dynamics are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Male partners likely need more information about SC methods, and identifying SC methods that men are comfortable with is critical to their use. While a study in South Africa with MLHIV who desired children found that men were enthusiastic for a clinic-based SC intervention [ 79 ], they also found structural barriers to participating in clinic-based interventions [ 87 ]. HIV-negative men in sero-different relationships may be reluctant to visit health centers for SC information and counseling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HIV PrEP was not yet available in or recommended as part of safer conception care in South Africa at the time this study was conducted. We developed a counseling tool that integrates relevant illustrations to simplify and explain key medical concepts ( Figure 1 ) [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, the reproductive goals of people with HIV, especially men, are not discussed as part of routine clinical care. Men with HIV who want to have children feel stigmatized and are unlikely to ask providers for advice [ 16 , 17 ], and few people with HIV are aware of the opportunities to meet reproductive goals without HIV transmission [ 18 - 21 ].…”
Section: Introductionmentioning
confidence: 99%